The natural history of weasels and stoats ecology, behavior, and management - King, C. M. (Carolyn M.); Powell, Roger A. (Oxford : Oxford University Press, 2007)
Both kinds of knowledge are brought together - observations for the traditional naturalist and rigorous measurements and interpretations for modern scientists, integrated into a single, readable account. This edition provides a comprehensive summary of the extensive advances over the last 15 years.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Weasels; Ermine